Different mechanisms involved in the berberine‐induced antiproliferation effects in triple‐negative breast cancer cell lines. Issue 8 (7th April 2019) - Lin, Yen‐Shu; Chiu, Yi‐Chou; Tsai, Yi‐Hsiu; Tsai, Yi‐Fang; Wang, Jir‐You; Tseng, Ling‐Ming; Chiu, Jen‐Hwey
Abstract: Background/Aim: Berberine (BBR) is known to be effective at inhibiting cell proliferation and promoting apoptosis in various cancer cells. However, the effects of BBR on triple‐negative breast cancer (TNBC) cells remain unclear. The aim of this study was to investigate the cell inhibition effects of BBR on different subtypes of TNBC cells. Methods: Using human TNBC cell lines of different subtypes, namely, MDA‐MB‐231, MDA‐MB‐468, MDA‐MB‐453, and BT‐549 as in vitro models, antiproliferative effects of BBR were investigated by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay, trypan blue exclusion assay, and clonogenic assay. Furthermore, cell apoptosis and autophagy were analyzed by flow cytometry, immunofluorescent staining, and LC3 I/II‐targeted Western blotting. Various cell growth‐related signaling pathways (AKT/ERK/p38) and the expression of proteins present in various cell cycle kinase complexes were analyzed by Western blotting. Results: BBR concentration‐dependently suppressed cell proliferation in MDA‐MB‐468 (0, 3, 6, and 12 μM) and MDA‐MB‐231 (0, 6.25, 12.5, and 25 μM). The inhibitory effect was not brought about by inducing cell apoptosis, necrosis, or autophagy. Cell cycle analysis disclosed an increased S+G2/M fraction among the BBR‐treated MDA‐MB‐231 and MDA‐MB‐453 cells; while with the BBR‐treated MDA‐MB‐468 and BT‐549 lines, an increased G0/G1 fraction was found. In MDA‐MB‐231 and MDA‐MB‐453 cells, by Western blotting, BBR decreased the expression of Cyclin A and CDK1, On the other hand, in BBR‐treated MDA‐MB‐468 and BT‐549 cells, there was a decrease in Cyclin D and CDK4 expression. Conclusion: Our results demonstrate that the antiproliferation effects of BBR occur via different mechanisms in different subtypes of TNBC cells, which suggests that BBR has potential as a personalized treatment for TNBC patients. Abstract : Our results demonstrate that the antiproliferation effects of berberine (BBR) occur via different mechanisms in the four representative triple‐negative breast cancer (TNBC) cell lines, which suggests that BBR has potential as a personalized treatment for TNBC patients